2022
DOI: 10.3389/fimmu.2022.944591
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals the metabolic regulators of duodenal low-grade inflammation in a functional dyspepsia model

Abstract: Several gastrointestinal phenotypes and impairment of duodenal mucosal barrier have been reported in clinical studies in patients with functional dyspepsia (FD). Due to the preferential colonization of the mucosa, intestinal microbes and their metabolites are commonly involved in host metabolism and immune responses. However, there are no studies on the intertwined correlation among multi-level data. For more comprehensive illustrating, a multi-omics analysis focusing on the duodenum was performed in the FD ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Then, the transcriptomes from all samples were merged to reconstruct a comprehensive transcriptome using Perl scripts. After the final transcriptome was generated, StringTie ( Ji et al., 2023 ) and Ballgown ( Leek, 2014 ) were used to estimate all transcript expression levels. Simply put, it is used to determine mRNA expression levels by calculating the fragments per kilobase of transcript per million mapped reads (FPKM).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the transcriptomes from all samples were merged to reconstruct a comprehensive transcriptome using Perl scripts. After the final transcriptome was generated, StringTie ( Ji et al., 2023 ) and Ballgown ( Leek, 2014 ) were used to estimate all transcript expression levels. Simply put, it is used to determine mRNA expression levels by calculating the fragments per kilobase of transcript per million mapped reads (FPKM).…”
Section: Methodsmentioning
confidence: 99%
“…The gut microbiota emerges as a pivotal determinant for changes in certain metabolites. Previous studies have reported the impact of alterations in duodenal microbiota on gastric emptying and mild duodenal inflammation in patients with FD [10,11]. Notably, probiotics have been suggested as a promising therapeutic approach for FD [12,13].…”
Section: Introductionmentioning
confidence: 99%